MICROBIAL COMMUNITIES OF THE KULDUR THERMAL SPRINGS AND THEIR PARTICIPATION IN THE ACCUMULATION OF MICROELEMENTS AND MINERAL FORMATION - Elena G. Lebedeva; Natalya A. Kharitonova; Ivan V. Bragin; Tatyana V. Kuzmina (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Relevance. Despite long-term regime observations of the temperature and chemical composition of thermal waters, there is practically no information about the microorganisms inhabiting thermal waters and bacterial mats and their biogeochemical role. Purpose: to study the composition, the number of functional groups of bacteria in water and in microbial mats formed in different temperature zones and to investigate their role in the accumulation of trace elements and the formation of minerals in the Kuldur thermal springs. The objects of study were the thermal underground waters of the Kuldur deposit of the following wells no. 1-87, 2-87, 3-87, 3-51, 5-51, as well as microbial mats formed in lakes and streams along the outflow of the Kuldur thermal springs. Methods: chemical and microbiological methods. To analyze the contents of microelements in water, the samples were analyzed using an inductively coupled plasma mass spectrometer. Determination of the content of chlorophyll a in microbial mats was carried out spectrophotometrically in ethanol extracts. The number of different physiological groups of bacteria was determined on various selective media by the Koch method and limiting dilutions. Cultures were cleaned by the exhaustive stroke method. Elemental analysis of microbial mats was performed by the ISP-MS method on a spectrometer. The phase composition of minerals was determined using X-ray phase analysis on a diffractometer. Results. It is shown that the thermal waters of the studied wells are alkaline, low mineralized, sodium predominates in the composition of cations, chlorine, fluorine and sulfate ions prevail among anions. Lithium, arsenic, and strontium dominate among microelements. In the studied wells of thermal waters, a low number of bacteria of various physiological groups was noted, while their number was higher in lower temperature waters. In microbial mats of different thermal zones, a different composition of physiological groups of bacteria was noted. Microorganisms of the geochemical cycle of sulfur, iron and manganese prevailed. The presence of cyanobacteria, which are characterized by the presence of chlorophyll a, was shown in the composition of all selected mats. A significant accumulation of many rare earth elements (especially light) – vanadium, as well as uranium and thorium by microbial communities – was revealed. In microbial mats, silicon was predominantly deposited in the form of quartz and plagioclase.